Mechanistic insights into glycoside 3-oxidases involved in C-glycoside metabolism in soil microorganisms - Taborda, André (2023)
Funding Information: We thank Diana Santos for preliminary data, Teresa Catarino with stopped-flow analysis, Tiago N. Cordeiro for help with Rosetta, Philippe Carpentier for support with krypton high-pressure experiments, Pedro Matias and Maximino Manzanera for valuable discussions. We thank the beamline staff at ESRF (Grenoble, France) and ALBA (Barcelona, Spain) for their support during the synchrotron data collection and Teresa Silva and Cristina Timóteo (Research Facilities, ITQB-NOVA) for technical assistance. The NMR data were acquired at CERMAX, ITQB-NOVA, Oeiras, Portugal, with equipment funded by FCT, project AAC 01/SAICT/2016. This work was supported by the Fundação para a Ciência e Tecnologia, Portugal, grants, 2022.02027.PTDC (L.O.M.), MOSTMICRO-ITQB (UIDB/04612/2020 and UIDP/04612/2020) (L.O.M. and M.R.V.), LS4FUTURE Associated Laboratory (LA/P/0087/2020) (L.O.M. and M.R.V.), PTDC/BII-BBF/29564/2017 (L.O.M.), UIDB/04326/2020, UIDP/043226/2020 and LA/P/0101/2020 (EPM) and FCT PhD fellowships 2020.07928 (A.T.), 2022.13872 (T.F.), and 2022.09426 (M.V.R.). B-Ligzymes (GA 824017) from the European Union’s Horizon 2020 Research and Innovation Program is also acknowledged for funding T.F. secondment at Zymvol and F.S. secondment at ITQB NOVA. L.M. and X.F.L. acknowledge PID2021-126897NB-I00 project and PRE2019-088412 fellowship, funded by MCIN/AEI/10.13039/501100011033/ FEDER, EU. Funding Information: We thank Diana Santos for preliminary data, Teresa Catarino with stopped-flow analysis, Tiago N. Cordeiro for help with Rosetta, Philippe Carpentier for support with krypton high-pressure experiments, Pedro Matias and Maximino Manzanera for valuable discussions. We thank the beamline staff at ESRF (Grenoble, France) and ALBA (Barcelona, Spain) for their support during the synchrotron data collection and Teresa Silva and Cristina Timóteo (Research Facilities, ITQB-NOVA) for technical assistance. The NMR data were acquired at CERMAX, ITQB-NOVA, Oeiras, Portugal, with equipment funded by FCT, project AAC 01/SAICT/2016. This work was supported by the Fundação para a Ciência e Tecnologia, Portugal, grants, 2022.02027.PTDC (L.O.M.), MOSTMICRO-ITQB (UIDB/04612/2020 and UIDP/04612/2020) (L.O.M. and M.R.V.), LS4FUTURE Associated Laboratory (LA/P/0087/2020) (L.O.M. and M.R.V.), PTDC/BII-BBF/29564/2017 (L.O.M.), UIDB/04326/2020, UIDP/043226/2020 and LA/P/0101/2020 (EPM) and FCT PhD fellowships 2020.07928 (A.T.), 2022.13872 (T.F.), and 2022.09426 (M.V.R.). B-Ligzymes (GA 824017) from the European Union’s Horizon 2020 Research and Innovation Program is also acknowledged for funding T.F. secondment at Zymvol and F.S. secondment at ITQB NOVA. L.M. and X.F.L. acknowledge PID2021-126897NB-I00 project and PRE2019-088412 fellowship, funded by MCIN/AEI/10.13039/501100011033/ FEDER, EU. Publisher Copyright: © 2023, The Author(s).